2021
DOI: 10.3390/ijms22052641
|View full text |Cite
|
Sign up to set email alerts
|

Sitosterolemia: Twenty Years of Discovery of the Function of ABCG5ABCG8

Abstract: Sitosterolemia is a lipid disorder characterized by the accumulation of dietary xenosterols in plasma and tissues caused by mutations in either ABCG5 or ABCG8. ABCG5 ABCG8 encodes a pair of ABC half transporters that form a heterodimer (G5G8), which then traffics to the surface of hepatocytes and enterocytes and promotes the secretion of cholesterol and xenosterols into the bile and the intestinal lumen. We review the literature from the initial description of the disease, the discovery of its genetic basis, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 149 publications
0
16
0
Order By: Relevance
“…ABCG5 and ABCG8 together encode a heterodimeric ATP-binding cassette transporter that facilitates secretion of cholesterol and non-cholesterol sterols in the intestine and bile. High plasma campesterol levels might compete with cholesterol for ABCG5/ABCG8 transporters during biliary cholesterol secretion, resulting in decreased biliary cholesterol levels and reduced risk of gallstones 49 , 50 (Supplementary Fig. 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…ABCG5 and ABCG8 together encode a heterodimeric ATP-binding cassette transporter that facilitates secretion of cholesterol and non-cholesterol sterols in the intestine and bile. High plasma campesterol levels might compete with cholesterol for ABCG5/ABCG8 transporters during biliary cholesterol secretion, resulting in decreased biliary cholesterol levels and reduced risk of gallstones 49 , 50 (Supplementary Fig. 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hayato Tada suggested that sitosterolemia can be diagnosed if the following conditions are all met at the same time ( 25 ): (1) clinical manifestations (xanthoma of skin or tendon); (2) laboratory tests (serum sitosterol ≥1 mg/dl); (3) familial hypercholesterolemia and cerebrotendinous xanthomatosis are excluded; (4) pathogenic mutations ABCG5 or ABCG8 . But the clinical manifestations of sitosterolemia are highly heterogeneous, although the genotype and phenotype lack an obvious correlation, and most laboratories lack conditions for phytosterol determination ( 26 ). Thus, at present, the diagnosis of this disease remains very difficult.…”
Section: Discussionmentioning
confidence: 99%
“…ABCG5 and ABCG8 together encode a heterodimeric ATP-binding cassette transporter that facilitates secretion of cholesterol and non-cholesterol sterols in the intestine and bile. High plasma campesterol levels might compete with cholesterol for ABCG5/ABCG8 transporters during biliary cholesterol secretion, resulting in decreased biliary cholesterol levels and reduced risk of gallstones 49,50 (Supplementary Fig. 11).…”
Section: Campesterol and Gallstones: Potential Causal Link Gallstones Affect 10-20%mentioning
confidence: 99%